Measuring the outcomes of volunteering for education: development and pilot of a tool to assess healthcare professionals' personal and professional development from international volunteering. Issue 7 (17th July 2019) - Tyler, Natasha; Collares, Carlos; Byrne, Ged; Byrne-Davis, Lucie
Abstract : Objective: The development and pilot of a self-report questionnaire, to assess personal and professional development of healthcare professionals gained through experiences in low-income and middle-income countries. Design: The instrument was developed from a core set of the outcomes of international placements for UK healthcare professionals. Principal component analysis and multidimensional item response theory were conducted using results of a cross-sectional pilot study to highlight items with the best psychometric properties. Setting: Questionnaires were completed both online and in multiple UK healthcare professional events face-to-face. Participants: 436 healthcare professional participants from the UK (with and without international experience) completed a 110-item questionnaire in which they assessed their knowledge, skills and attitudes. Measures: The 110-item questionnaire included self-report questions on a 7-point Likert scale of agreement, developed from the core outcome set, including items on satisfaction, clinical skills, communication and other important healthcare professional knowledge, skills, attitudes and behaviours. Item reduction led to development of the 40-item Measuring the Outcomes of Volunteering for Education-Tool. Internal consistency was evaluated by the Cronbach's α coefficient. Exploratory analysis investigated the structure of the data using principal component analysis and multivariate item response theory. Results: Exploratory analysis found 10 principal components that explained 71.80% of the variance. Components were labelled 'attitude to work, adaptability, adapting communication, cultural sensitivity, difficult communication, confidence, teaching, management, behaviour change and life satisfaction'. Internal consistency was acceptable for the identified components (α=0.72–0.86). Conclusions: A 40-item self-report questionnaire developed from a core outcome set for personal and professional development from international placements was developed, with evidence of good reliability and validity. This questionnaire will increase understanding of impact of international placements, facilitating comparisons of different types of experience. This will aid decision making about whether UK healthcare professionals should be encouraged to volunteer internationally and in what capacity.